2020
DOI: 10.1016/j.ijid.2020.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammatory markers with the severity of COVID-19: A meta-analysis

Abstract: Objectives: Studies reported associations of inflammatory markers with the severity of COVID-19, but conclusions were inconsistent. We aimed to provide an overview of the association of inflammatory markers with the severity of COVID-19. Methods: We searched PubMed, Embase, Cochrane Library, Wanfang and China National Knowledge Infrastructure (CNKI) database until March 20, 2020. Weighted mean difference (WMD) and 95% confidence intervals (CIs) were pooled using random or fixed-effects models. Results: A total… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
532
9
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 578 publications
(591 citation statements)
references
References 32 publications
32
532
9
18
Order By: Relevance
“…In the case of heterogeneity among studies (I 2 > 50% or P < 0.1), random-effect model was used and would give a more conservative estimate of the 95% CI. In other cases, fixed-effect model was adopted (I 2 ≤ 50% and P ≥ 0.1) [22] . Sensitivity analysis was performed by omitting one study each time through influence analysis to assess the stability of results.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of heterogeneity among studies (I 2 > 50% or P < 0.1), random-effect model was used and would give a more conservative estimate of the 95% CI. In other cases, fixed-effect model was adopted (I 2 ≤ 50% and P ≥ 0.1) [22] . Sensitivity analysis was performed by omitting one study each time through influence analysis to assess the stability of results.…”
Section: Methodsmentioning
confidence: 99%
“…No differences were found in serum ferritin levels at 1 month between the three groups, suggesting that hyperin ammatory state was controlled to a similar degree in all patients regardless of their immunosuppressive treatment [36]. Although elevated ferritin levels have been considered a clinical factor associated with a poor prognosis in patients with cytokine storm [37], we observed no betweengroup differences in the association between serum ferritin levels and mortality -a nding probably related in part to the fact that the elevation in ferritin was moderate in all patients in the present cohort.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that CRP levels are positively related to the severity of COVID-19 19 . Another study illustrated a high ESR level in patients suffering severe COVID-19 symptoms when compared to nonsevere groups, due to an increase in in ammation in severely affected patients 14 . In addition, other studies considered the serum albumin level as a vital indicator in severe COVID-19 patients 16,20 .…”
Section: Introductionmentioning
confidence: 96%
“…Several biological markers have been found to correlate with the severity of COVID-19, including high Creactive protein (CRP) level, high erythrocyte sedimentation rate (ESR) level and low level of serum albumin (hypoalbuminemia) 8, [14][15][16] . These biomarkers in parallel with the clinical symptoms can be used to interpret more con dently the likely progression and severity of the disease 17 .…”
Section: Introductionmentioning
confidence: 99%